2014
DOI: 10.3178/hrl.8.27
|View full text |Cite
|
Sign up to set email alerts
|

Projected hydrological changes and their consistency under future climate in the Chao Phraya River Basin using multi-model and multi-scenario of CMIP5 dataset

Abstract: Abstract:It is important to examine what future hydrological changes could occur as a result of climate change. In this study, we projected hydrological changes and their consistency under near-future and end-of-21st-century climate in the Chao Phraya River Basin. Through hydrological simulations using output from six AOGCMs under the RCP 4.5 and 8.5 scenarios, we have reached the following conclusions. Our results demonstrate a projected increase in mid-rainy season precipitation under future climate, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
2
15
1
Order By: Relevance
“…The findings from the analysis of the projected river discharge at the Nakhon Sawan station (C.2 station) are as follows: 1) the mean monthly discharge tends to increase in both the near-future and far-future projection periods for all months; 2) low-flow exceeding 99% of a mean daily flow duration curve for the near-future and far-future periods tends to decrease; and 3) a flood frequency analysis with the GEV distribution using the annual maximum daily flow series indicates that the flood risk in the near-future and far-future projection periods becomes higher. These findings of our study are compatible with the previous studies by Hunukumbura and Tachikawa (2012), Kure and Tebakari (2012), Kotsuki et al (2014), and Watanabe et al (2014). The result is different from the study by Champthong et al (2013), which may arise from the difference of used GCM outputs, with and without bias correction for input data, and different hydrologic model settings.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The findings from the analysis of the projected river discharge at the Nakhon Sawan station (C.2 station) are as follows: 1) the mean monthly discharge tends to increase in both the near-future and far-future projection periods for all months; 2) low-flow exceeding 99% of a mean daily flow duration curve for the near-future and far-future periods tends to decrease; and 3) a flood frequency analysis with the GEV distribution using the annual maximum daily flow series indicates that the flood risk in the near-future and far-future projection periods becomes higher. These findings of our study are compatible with the previous studies by Hunukumbura and Tachikawa (2012), Kure and Tebakari (2012), Kotsuki et al (2014), and Watanabe et al (2014). The result is different from the study by Champthong et al (2013), which may arise from the difference of used GCM outputs, with and without bias correction for input data, and different hydrologic model settings.…”
Section: Discussioncontrasting
confidence: 42%
“…Champathong et al (2013) assessed the uncertainty of river flow projections using the outputs of MRI-AGCM3.1S and MRI-AGCM3.1H. Kotsuki et al (2014) found the increase of runoff at the Nakhon Sawan area using a land surface model forced by outputs from six biascorrected CMIP5 GCMs. Watanabe et al (2014) projected natural river flow using newly developed bias-corrected outputs of nine GCMs and showed the increase of future river discharge in September to reference simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The climate of the basin can be clearly divided into dry and wet seasons. The precipitation from May to October accounts for almost 90% of the total annual precipitation (Kure and Tebakari, 2012), and precipitation is generally higher in the northern mountainous area compared to other areas (Kotsuki et al, 2014).…”
Section: The Chao Phraya River Basinmentioning
confidence: 99%
“…The H08 hydrological model requires daily temperature, precipitation, long-and short-wave radiation, specific humidity, surface pressure, and wind speed data. We used data from the IMPAC-T forcing dataset (IFD) developed by Kotsuki et al (2014) as the atmospheric forcing for the hydrological simulation of the reference period (1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999). The IFD is a daily forcing dataset at 5-arc-minute resolution based on in situ observations and reanalysis data.…”
Section: Atmospheric Forcing Datamentioning
confidence: 99%
“…As improvement of climate projections through CMIP3 to CMIP5, various impact studies have been implemented to predict the alterations of water resources under climate change (Jung et al, 2013;Kotsuki et al, 2014;Apurv et al, 2015;Steinschneider et al, 2015;Cao et al, 2016;Venkataraman et al, 2016). However, hydrologic projections include considerable uncertainties from selection of emission scenarios, AOGCM models, statistical downscaling, and hydrologic models (Murphy et al, 2004;Wilby and Harris, 2006;Kay et al, 2009;Chen et al, 2011;Poulin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%